Tinjauan Psikologis Tentang Anarkisme dan Bughat - Hasmita Jannah (Program Studi Psikologi Fakultas Kedokteran Universitas Malikussaleh, 2019)
Anarchism is an ideology in which individuals are socialized without government. Individuals more maintain their creativity in a country. Here the concept of anarchism is similar to the concept of bughat. Bughat is a group that opposes the government or opts out of the government. But there is also a difference between the two, anarchism is more understanding to feel free, not to be arranged and he wants to always rebel his government if he feels not in accordance with what he wants. While this bughat form of rebellion action of his government. This study aims to mebuat comparison or comparison of the two concepts because basically these two concepts have similarities that are so real and can be said the same, but there are alsodifferences that make the concept is not the same. This study comes from various information from both concepts such as from social media and journals. This study makes us understand what the comparison between the two concepts.